Philippine Automated Water Information System Concepts and Structure. - Resurreccion, Alejandro N., Jr (Philippine Engineering Journal)
The Philippine Automated Water Information System is a computer-based system for the storage, retrieval and analysis of water data. It is aimed to provide a systematic and more efficient means of data accumulation and dissemination. The system is divided into three components, namely : Data Management component which is responsible for the creation and maintenance of its requisite files, Data Retrieval component which is responsible in satisfying the user's request for data and the Data Analysis component which is responsible in providing the user with the results of processing and analyzing data.